Assessment in Transformation - Eva Insulander; Patrik Hernwall; Anna Åkerfeldt; Elisabeth Öhman (Educare)
Using data from focus group interviews, this study aims to analyze the perceived opportunities and challenges encountered by groups of secondary school teachers regarding the assessment of multimodal texts. Previous research has shown that digital technologies introduce new kinds of texts in the classroom. The possibility of combining verbal text with image, sound, and movement has an impact on students’ text production. However, the changing role of writing on the screen has left teachers uncertain of how to assess these new forms of texts. Apart from attending to digital competence, assessing multimodal texts may involve following writing conventions and organizing text using different resources and components. Quality in multimodal texts may concern using multimodal components to communicate complex ideas effectively, which may or may not be noticed by teachers. The data is based on group interviews with 11 secondary school teachers at two different schools. The study conducted a thematic content analysis using the analytical concepts of transformation, recognition, design, and form and meaning. Findings show that teachers find it challenging to acknowledge certain qualities in students’ multimodal texts without support from the steering documents. On the other hand, they notice opportunities to follow students’ learning processes. In addition, they stress an increased opportunity and need for shared assessment across school subjects. The article concludes with a discussion of tensions regarding opportunities and challenges when assessing students’ multimodal texts in relation to the different subject syllabuses.